2015
DOI: 10.4103/0019-5049.160933
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Episure™ AutoDetect™ syringe versus glass syringe for identification of epidural space in lower thoracic epidural

Abstract: Background and Aims:Episure™ AutoDetect™ syringe (EAS), a spring-loaded syringe, is a new loss-of-resistance syringe used to identify epidural space. It has an advantage of subjective and objective confirmation in identifying epidural space over glass syringe (GS) for beginners. We compared the performance of EAS with that of GS for identifying epidural space in lower thoracic epidurals.Methods:A total of 120 American Society of Anesthesiolgists I-II patients aged 18–60 years requiring lower thoracic epidural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Epimatic® is a low-resistance syringe where continuous positive pressure on the plunger is achieved by an elastic strip. When the Tuohy needle enters the epidural space, LOR is visible by the sudden movement of the syringe plunger, which removes operator subjectivity and variability [14]. The other advantage of the spring-loaded syringe is that both hands can be used for needle's advance and stabilization [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epimatic® is a low-resistance syringe where continuous positive pressure on the plunger is achieved by an elastic strip. When the Tuohy needle enters the epidural space, LOR is visible by the sudden movement of the syringe plunger, which removes operator subjectivity and variability [14]. The other advantage of the spring-loaded syringe is that both hands can be used for needle's advance and stabilization [15].…”
Section: Discussionmentioning
confidence: 99%
“…There was one accidental dural puncture in the control group [19]. The literature offers reports on 3 other syringes with a similar mechanism of action (constant positive-pressure for the automated EPD identification), namely (i) Episure™ AutoDetect™ syringe, Indigo Orb, Inc., Santa Clara, California, United States [14,15,[20][21][22] (ii) Epidrum, Emooor Innovations Ltd. Taunton, United Kingdom [13,[22][23][24][25][26][27][28] and (iii) Epi-Jet, Egemen International, Izmir, Turkey [13,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, it consists of a syringe embedding a coaxial compression; the plunger automatically depresses when the needle enters epidural space, providing a visual confirmation of LOR. This system has been validated in clinical settings with promising results: in a pilot study performed in 168 parturients there was no failure during the epidural blockade .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the introduction of new techniques aiming to have an objective detection of the LOR, and, in many cases, these investigations have led to commercial devices .…”
mentioning
confidence: 99%